2009
DOI: 10.1128/iai.00334-09
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Pathogenesis of Spores from the Human Fungal PathogenCryptococcus neoformans

Abstract: Cryptococcus neoformans was first described as a human fungal pathogen more than a century ago. One aspect of the C. neoformans infectious life cycle that has been the subject of earnest debate is whether the spores are pathogenic. Despite much speculation, no direct evidence has been presented to resolve this outstanding question. We present evidence that C. neoformans spores are pathogenic in a mouse intranasal inhalation model of infection. In addition, we provide mechanistic insights into spore-host intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
187
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(195 citation statements)
references
References 46 publications
3
187
0
5
Order By: Relevance
“…We observed that yeast cells mixed with spores could be phagocytosed by macrophages when spores were also present. These observations confirm and extend the previously reported findings of Giles et al, who discovered that spores do not require opsonin to be phagocytosed by macrophages (15). We postulate that ␤-1,3-glucans on spores and acapsular yeast cells are readily exposed to dectin 1, leading to rapid phagocytosis by macrophages.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We observed that yeast cells mixed with spores could be phagocytosed by macrophages when spores were also present. These observations confirm and extend the previously reported findings of Giles et al, who discovered that spores do not require opsonin to be phagocytosed by macrophages (15). We postulate that ␤-1,3-glucans on spores and acapsular yeast cells are readily exposed to dectin 1, leading to rapid phagocytosis by macrophages.…”
Section: Discussionsupporting
confidence: 82%
“…As positive and negative controls, unopsonized yeast cells and yeast cells opsonized with monoclonal antibody 18B7, respectively, were assessed in parallel. Giles et al recently found that spores do not require opsonization for phagocytosis (15). Our findings confirm their conclusions, and phagocytosis of unopsonized C. neoformans spores was clearly observed under our experimental conditions (see Movie S1 in the supplemental material), with the first phagocytosis events being detected by 55 min postincubation.…”
Section: Vol 77 2009supporting
confidence: 80%
“…Gat1 negatively regulates mating in both mating-type a and a strains: During nitrogen limiting or starvation conditions, C. neoformans can undergo sexual reproduction that leads to the production of potentially infectious air-borne basidiospores (Kwon-Chung 1976; Lengeler et al 2000;Giles et al 2009). To address whether Gat1 plays a role in this sexual development, we created a gat1D derivative of MATa C. neoformans strain KN99a (VNI) by replacing the GAT1 ORF with the nourseothricin acetyl-transferase (NAT ) selectable marker, to serve as a mating partner for our existing gat1::NEO of MATa strain H99.…”
Section: Resultsmentioning
confidence: 99%
“…By definition, a basidiomycete fungus (e.g., Cryptococcus neoformans) produces hyphal structures during sexual differentiation that distinguish it from ascomycetes (Kwon-Chung 1975, 1976. Spores produced by Cryptococcus hyphae are quite infectious and may be the primary particle inhaled during a natural infection (Giles et al 2009;Velagapudi et al 2009). Therefore, the transition to hyphal growth that supports sporulation is required for the wide dissemination of Cryptococcus in the environment, as well as for infection of its mammalian hosts.…”
Section: Yeast Morphogenesis In a Basidiomycetementioning
confidence: 99%